The Role of the 2013 Curriculum Assessment Standards in Improving the Quality of Education - Febriyanti, Febriyanti; Ayu Amelia; Abdurrahmansyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The 2013 Curriculum has significantly brought changes to the Indonesian education system by emphasizing integrated assessment covering cognitive, affective, and psychomotor domains to produce competent graduates with strong character. This study aims to examine the implementation of the 2013 Curriculum assessment standards, identify challenges faced by educators, and formulate strategic solutions to improve the quality of assessment. Using a qualitative descriptive approach, the research involves a purposive sample of elementary school teachers who implement authentic assessment methods. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed thematically. The results indicate that while the standards provide a systematic framework for comprehensive assessment, limitations such as teachers' insufficient competencies, high workload, lack of training, and limited technology hinder effective implementation. The study concludes that there is a need to enhance teachers' capacity through continuous training, integrate technology in assessment, and simplify assessment instruments as steps to optimize assessment practices. These findings contribute valuable insights for education stakeholders to strengthen assessment practices to improve the quality of learning in Indonesian schools.